A comunidade zooplanctônica de rios amazônicos na área de influência da Usina Hidrelétrica de Santo Antônio do Madeira, RO: diferentes abordagens no monitoramento - Silva, Lidiane Cristina da (Universidade Federal de São Carlos, 2015)
The growing world interest for the Amazon region has risen up the most diverse issues. Among these are those of ecological importance, to promote the conservation and maintenance of natural resources of the region. It was intended to, in this study, analyze the structure of the zooplankton community and its spatial distribution and temporal patterns on the Madeira River and tributaries in the area of influence of the Santo Antônio HPP, before, during and after their deployment, to verify the occurrence possible changes. Quarterly samplings were carried out for four years for the physical and chemical variables and zooplankton. The zooplankton community structure varied widely depending on the hydrological events, but was little changed after filling the reservoir probably because the HPP be of the run-of-river type. Changes in the density of zooplankton were lower than those observed in large accumulation reservoir previously built in the Amazon. However there have been changes in the proportions of biomass of different zooplankton groups. Whereas the functional approach, in all analyzed rivers was observed that before the filling had greater selection of r strategists and smaller species and after filling greater numbers of functional groups coexisted. In relation to the components of diversity, greater evenness values were recorded in the last years of sampling. For other functional and taxonomic indices (richness, Shannon, FDis and FEev), differences related to impoundment on the Madeira River were not verified. Considering the approach of surrogates, the amounts recorded for analysis of concordance between the zooplankton community groups and also among the taxonomic classification levels were low significance, which prevents them from being used separately in biomonitoring studies in the region. We conclude that the Madeira River and its tributaries have high zooplankton diversity and until the moment the changes in the community were low, presumably by maintaining the short residence time. The results show that different approaches, both functional as taxonomic, evaluated together, can be a great step toward understanding the relationship between environmental standards, management practices and production of ecosystem services.
Keywords: Zooplâncton; Madeira, Rio (RO e AM); Usinas hidrelétricas; Diversidade funcional; Suficiência taxonômica; Suficiência numérica; Madeira River; Zooplankton; Functional diversity; Surrogates; Taxonomic suficiency; Numeric suficiency; CIENCIAS BIOLOGICAS::ECOLOGIA